IMPLEMENTATION OF A SERVICE FOR PEOPLE WITH PELVIC FLOOR DISORDERS - Sampaio, Luis Rafael Leite; Sousa, Francisca Clarisse de; Dantas, Tays Pires; Pereira, Natannael da Silva; Meneses, Lucas Cosmo de; Alves, Luana de Souza; Souza, José Lucas de; Alves, Cicera Clareliz Gomes; Rocha, Gislaine da Silva; Penha, Sarah Emanuelle Matias; Tomé, Francisco Vinícius; Alves, Francisco Pereira; et al. (Estima – Brazilian Journal of Enterostomal Therapy, 2022)
Objective: the objective was to describe the technical operational procedures and clinical data related to the implementation of a health care program for people with pelvic floor disorders in a public secondary care service. Method: this is an experience report, based on experiences related to academic and professional assistance in the implementation of a service aimed at pelvic floor disorders in the Cariri region of Ceará, carried out from May to July 2021. Results: for the implementation of the service, the following strategies were adopted: tracking the health care network for people with pelvic floor disorders; organizational structuring of the service; capturing people with pelvic dysfunctions; start of care; and therapeutic follow-up. Conclusion: in view of the above, it is evident that the health care program for people with pelvic floor disorders could be implemented satisfactorily, considering the infrastructure, the significant amount of care provided and the therapeutic follow-up achieved. Thus, with this report, it is expected to contribute to the development of new outpatient services aimed at this area of work of the stomatherapist nurse and the multidisciplinary team.